Peningkatan sikap sosial melalui model pembelajaran kooperatif tipe group investigation (GI) dalam pembelajaran IPS di sekolah dasar - Ummu Khasanah; Hadi Mulyono; Hadiyah Hadiyah (Universitas Sebelas Maret, 2022)
This study aims to improve students social attitudes by applying the Group Investigation (GI) type of cooperative learning model. This research is a Classroom Action Research with two cycles. Grade IV students of SD Negeri Tegalsari No. 60 Surakarta academic year 2019/2020 totaling 24 students. Data collections techniques in the form of interviews, observation, and documentation. Data analysis used triangulation of sources and techniques. The results of the observation showed that the social attitudes of students in the very good category were 11 students (45.83 %) which increased in the first cycle by 14 students (58.33 %) and increased in the second cycle as many as 21 students (85.42 %) who had social attitudes in the very good category. Based on the results of these studies, it can be concluded that the application of the Group Investigation (GI) cooperative learning model can improve students social attitudes. This research contributes to being used as a reference in the development of various learning activities on social studies subjects.